2017
DOI: 10.1161/circimaging.116.004897
|View full text |Cite
|
Sign up to set email alerts
|

Functional Tricuspid Regurgitation Caused by Chronic Atrial Fibrillation

Abstract: Background— Functional tricuspid regurgitation (TR) with a structurally normal tricuspid valve (TV) may occur secondary to chronic atrial fibrillation (AF). However, the clinical and echocardiographic differences according to functional TR subtypes are unclear. Therefore, characterization of functional TR because of chronic AF (AF-TR) remains undetermined. Methods and Results— To investigate the prevalence of AF-TR, 437 patients with mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(60 citation statements)
references
References 25 publications
(26 reference statements)
2
58
0
Order By: Relevance
“…Although 2D echocardiography is widely used in clinical practice and also for research currently, especially for patients with AF, 2D images lacked from inherent limitations such as incomplete comprehension of 3D tricuspid annulus. 3D echocardiography with one beat acquisition might provide more accurate measurements with more reproducible landmarks and could be used to confirm the present findings in further studies [ 33 , 34 ]. Thirdly, in our subgroup analysis, although propensity-score matching adjusts for baseline imbalances, the analysis does not control for unmeasured confounders.…”
Section: Discussionsupporting
confidence: 78%
“…Although 2D echocardiography is widely used in clinical practice and also for research currently, especially for patients with AF, 2D images lacked from inherent limitations such as incomplete comprehension of 3D tricuspid annulus. 3D echocardiography with one beat acquisition might provide more accurate measurements with more reproducible landmarks and could be used to confirm the present findings in further studies [ 33 , 34 ]. Thirdly, in our subgroup analysis, although propensity-score matching adjusts for baseline imbalances, the analysis does not control for unmeasured confounders.…”
Section: Discussionsupporting
confidence: 78%
“…AF leads to atrial enlargement and dilatation of mitral and tricuspid annuli [ 4 ]. Advanced age and right heart enlargement have been associated with atrial FTR [ 8 , 18 , 20 ]. Furthermore, some echocardiographic parameters are related to TR severity in patients with AF, such as LAV index, tricuspid annular diameter, tenting height, right atrial area, PASP and RV remodeling [ 8 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age and right heart enlargement have been associated with atrial FTR [ 8 , 18 , 20 ]. Furthermore, some echocardiographic parameters are related to TR severity in patients with AF, such as LAV index, tricuspid annular diameter, tenting height, right atrial area, PASP and RV remodeling [ 8 , 25 ]. Apart from the echocardiographic parameters related to right heart remodeling, the present study demonstrated that female gender, LAV index and PH were independently associated with significant FTR in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Besides that, there is evidence that atrial fibrillation (Afib) and right ventricular (RV) pacing may also be of pathophysiological importance. [3][4][5] While significant reflux may be well tolerated for years TR is often neglected. However, literature suggests significant TR is associated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%